Pengaruh Program Pertukaran Mahasiswa Merdeka terhadap Kreativitas dan Kemandirian Mahasiswa Universitas Prima Indonesia - Palma Juanta; Muhamad Gus Amix Kusuma; Isabel Patricia; Muhammad Arifin Hidayat (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
The Merdeka Student Exchange Program (PMM) 4 Inbound at Universitas Prima Indonesia aims to enrich the academic and personal experiences of students by providing them with the opportunity to study in a different environment. This research analyzes the impact of the Merdeka Student Exchange Program (PMM) on the creativity and independence of PMM 4 Inbound students at Universitas Prima Indonesia during the even semester of the 2023/2024 academic year. The research method used is quantitative, employing a questionnaire as the instrument. The sample consists of 50 students selected through simple random sampling. The results indicate that PMM significantly enhances the creativity and independence of students. The implications of this research provide important insights for the development of similar programs at other higher education institutions.